Biosynthesis of bionanomaterials using Bacillus cereus for the recovery of rare earth elements from mine wastewater. (1st March 2023) - Yan, Qiuting; Lin, Xiaoyu; Chen, Zhibiao; Chen, Zuliang
Abstract: The growing demand for rare earth elements (REEs) increasingly requires secondary resources such as mine wastewater containing high concentrations of REEs, to be used as a source of REEs. The current challenge is how to efficiently recover REEs from this feed source. In this paper, a functional bionanomaterial (FeNPs-EPS) was biosynthesized using Bacillus cereus as a possible means of recovering REEs. This composite was composed of both synthesized iron nanoparticles (FeNPs) and extracellular polymeric substances (EPS). Synthesis of the FeNPs-EPS composite via a one-step biosynthesis was confirmed by materials characterization. The peak in the material's UV–Vis spectra at 511 nm demonstrates the formation of FeNPs-EPS, where 3D-EEM showed that FeNPs-EPS was wrapped predominantly with tryptophan protein-like and humic acid-like substances. In addition, while FTIR indicated that the functional groups present in EPS where virtually identical to those observed in FeNPs-EPS, XPS demonstrated that Fe and O were the major elemental present as both FeO and Fe2 O3 . Zeta potential measurements indicated that FeNPs-EPS had good stability under different pH conditions, where BET analysis supported multilayer adsorption. Finally, on exposure to high concentrations of Eu(III) and Tb(III) in mine wastewater, the synthesized FeNPs-EPS demonstrated strong potential to remove two cations from the wastewater and hence a potentially practical way to efficiently recover REEs from such waste streams. Highlights: A FeNPs-EPS composite was prepared using Bacillus cereus. Function of FeNPs-EPS was based on synergistical effects. More than 92% of Eu(III) and Tb(III) from mine wastewater was recovered.